Associations between anthropometry, body composition, and body image in athletes: a systematic review - Webb, Mary D.; Melough, Melissa M.; Earthman, Carrie P.; Katz, Sarah E.; Pacanowski, Carly R. (Frontiers in Psychology, 2024)
Poor body image is a potent risk factor for disordered eating and eating disorders. Athletes are a population at increased risk for eating disorders despite reports of lower body image concerns compared to non-athletes. Body size and composition may influence an athlete's susceptibility to poor body image. Five electronic databases (PubMed, Cochrane Library, PsycINFO, Web of Science, SPORTDiscus) were searched to systematically evaluate the literature regarding the association between body measures (i.e., anthropometric and body composition indicators) and body image in athletes. The systematic review was completed following PRISMA guidelines, and 27 cross-sectional studies were identified for inclusion and evaluated using the Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross-Sectional Studies. Studies differed in methodological assessment of anthropometry or body composition (i.e., self-reported versus researcher-measured), methods for evaluating aspects of body image, geographic location, and sport type. Higher body mass index (BMI) or percent body fat (%BF) was significantly associated with greater body dissatisfaction in 16 of 22 studies (72.7%). Positive associations between body measures and aspects of negative body image were most consistently observed among studies that assessed BMI based on self-reported heights and weights, while significant associations between body composition measures (e.g., %BF, fat mass, fat-free mass) were less common. Four of seven studies assessing relationships between BMI and an aspect of positive body image reported significant inverse relationships, while three revealed insignificant associations. Overall, higher BMI and body fat were associated with body dissatisfaction among athletes. Future studies are needed to confirm these findings within focused populations and utilizing body composition methods (e.g., bioelectrical impedance techniques).